Analisis Unbalanced Load Flow pada Jaringan Listrik Pembangkit Listrik Tenaga Mikrohidro dengan Metode Injeksi Arus (Current Injection) - Maimun -; Fauzan -; Radhiah - (Jurnal Teknologi, 2017)
In this study the unbalanced load flow analysis with current injection method (current injection) is performed on the electrical grid amid lower that in the electricity grid micro hydro power (MHP) plant in order to determine the characteristics and efficiency of the electricity grid. The case studies carried out on the electrical grid  Cokro Tulung Klaten district. MHP Cokro Tulung the MHP stand alone (stand alone) airport beben-load is inductive beruapa AC electric motor 3 (three) phase that is used to pump water to the water-boom and loads such as lighting, also the burden of household appliances. Power flow studies in an unbalanced state or unbalaced load flow analysis with current injection method (current injection) is performed with the aid of a software program ETAP 7.0. Based on the results of the analysis result unbalaced load flow with the current injection method (current injection) has been done on the electrical grid MHP Cokro Tulung, it was found that the active power losses in total (ΔPT) arising on the power grid MHP full load current of 268.442 W or 0.714% of the total power (37.58 kW). Voltage drop occurs in sktr amounted to 1.123 V or 0.295% of its nominal voltage (380 V). Voltage drop occurs in SUTR respectively 6.994 V or 3.179% of its nominal voltage (220 V). So the power loss (ΔP) and the voltage drop (ΔV) arising on the power grid MHP Cokro Tulung is still small, so the efficiency of the electricity network is still quite good